Shaking Table Tests on Earthquake Response Characterization of a Complex Museum Isolated Structure in High Intensity Area - Wenguang Liu; Chuan Qin; Yang Liu; Wenfu He; Qiaorong Yang (Shock and Vibration)
Owing to special functional requirements of museum, such as great space and story height for exhibitions, large floor slab openings in plan and long span truss in elevation are becoming increasingly considered in museum design, which leads to challenges to structural safety. The aseismic performance of an isolated museum structure in high earthquake intensity regions was thus studied because of its complexity and irregularity. In order to observe the seismic characteristics and verify isolation effect, shaking table tests of a 1/30-scale structural model with and without base isolation bearings have been carried out under minor, moderate, and major earthquakes. The experimental results show that isolated structure dynamic characteristics and isolation effect are stable and storey peak acceleration responses of superstructure are less than that of fixed structure. Storey drifts of isolated structure meet required limits stipulated in Chinese design code and torsion responses of the bearings are not remarkable. It is suggested that seismic performances of complex museum structures have been effectively improved with isolation in use.